Unveiling the roles of lattice strain and descriptor species on pt-like oxygen reduction activity in Pd-Bi catalysts - Sarkar, Shreya; Ramarao, S. D.; Das, Tisita; Das, Risov; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (ACS Catalysis, 2021)
A facile non-template-assisted mechanical ball milling technique was employed to generate a PdBi alloy catalyst. The induced lattice strain upon the milling time caused a shift of the d-band center, thereby enhancing the oxygen reduction reaction (ORR) catalytic activity. Additionally, the Pd-O reduction potential and adsorbed OH coverage used as descriptors stipulated the cause of the enhanced ORR activity upon the increased milling interval. Redox properties of surface Pd are directly correlated with a positive shift in the Pd-O reduction potential and OH surface coverage. Hence, by deconvoluting the lattice strain and the role of the descriptor species we achieved a catalyst system with a specific activity 5.4X higher than that of commercial Pt/C, as well as an improved durability. The experimental observation is well-corroborated by a theoretical simulation done by inducing strain to the system externally.
Keywords: charge-transfer; electrocatalysis; fuel cell; Lattice strain; oxygen reduction; Pt-like activity